Analisis Tema dan Gaya Bahasa pada Puisi “Yang Kuminta Hanyalah” Karya Taufiq Ismail dan Puisi “Perempuan Yang Tergusur” Karya W.S Rendra - Junifer Siregar (Medan Resource Center, 2023)
This study aims to analyse the themes and language styles in the poems of Taufiq Ismail and W. S. Rendra, specifically focusing on the poems related to displaced women. The goal is to describe the themes and language styles present in each stanza of these poems. The data were collected in text format and organized into thematic and stylistic categories based on established literary theories. The theories employed include themes and language styles. The major themes found in both sets of poems include the portrayal of women's struggles and the broader themes of justice and violence. The language styles identified in Taufiq Ismail's poems include pleonasm, repetition, personification, climax, paradox, and allegory, with the most dominant style being pleonasm (occurring twice). In W. S. Rendra's poems about displaced women, the language styles encompass pralism, personification, paradox, pleonasm, allegory, metonymy, and symbolism. The most prevalent style is personification (occurring three times).